1979
DOI: 10.1128/aem.38.1.39-42.1979
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and iron addition to casein hydrolysate medium for production of staphylococcal enterotoxins A, B, and C

Abstract: From comparisons of 4% N-Z Amine NAK made with distilled water, naturally hard water, and synthetic salt solutions, it appeared that magnesium and, to a lesser extent, iron were limiting factors in the production of staphylococcal enterotoxins B and C but not A. Maximum enterotoxin production with NAK medium was achieved by the addition of 5 mg of Mg2" per liter (for a total of 9 mg of Mg2e per liter) and 0.5 mg of Fe2" per liter. Higher levels of magnesium were not inhibitory. Supplementing NAK with commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Relatively large amounts of SEB were produced with our medium. The yield achieved was comparable with those obtained by Kato et al (10) and Reiser and Weiss (14) but was much higher than that produced in the medium suggested by Morita et al (13). The good results obtained from our medium were not unexpected since this medium consists of pancreatic digest of casein, minerals, and vitamins which are all known to be important for the production of enterotoxin B (12,18).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Relatively large amounts of SEB were produced with our medium. The yield achieved was comparable with those obtained by Kato et al (10) and Reiser and Weiss (14) but was much higher than that produced in the medium suggested by Morita et al (13). The good results obtained from our medium were not unexpected since this medium consists of pancreatic digest of casein, minerals, and vitamins which are all known to be important for the production of enterotoxin B (12,18).…”
supporting
confidence: 85%
“…Several studies have shown that the optimal conditions for the production of Staphylococcus aureus enterotoxins are obtained with complex media such as casein hydrolysate (10,13,14). The commercial unavailability of most of these media, especially the recently used N-Z Amine-NAK caseine hydrolysate (M. S. Bergdoll, Food Research Institute, University of Wisconsin at Madison; personal communication), prompted us to search for a new and easily available medium for the production of enterotoxin B.…”
mentioning
confidence: 99%
“…Staphylococcus aureus is responsible for septicemia especially in neonates and the elderly. Like most pathogenic bacteria, S. aureus needs iron for growth and full expression of virulence [4,5]. We have been interested in the iron acquisition mechanisms used by this pathogen to cause septicemia, because one of the 0378-1097 / 98 / $19.00 ß 1998 Federation of European Microbiological Societies.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is responsible for septicemia especially in neonates and the elderly. Like most pathogenic bacteria, S. aureus needs iron for growth and full expression of virulence [4, 5]. We have been interested in the iron acquisition mechanisms used by this pathogen to cause septicemia, because one of the critical steps in the pathogenesis is the uptake of iron from blood.…”
Section: Introductionmentioning
confidence: 99%